Organ Tropism of Angiostrongylus vasorum Larval Stages in Infected African Giant Snails (Lissachatina fulica) - Dusch, Alena; Segeritz, Lisa; Henrich, Manfred; Taubert, Anja; Hermosilla, Carlos; Justus Liebig University Giessen (My University, 2024)
Angiostrongylus vasorum is a metastrongyloid lungworm causing severe cardiovascular disease in domestic and wild animals. During its heteroxenous life cycle, A. vasorum requires obligate gastropod intermediate hosts. Little is known about A. vasorum larval organ tropism and development in gastropod intermediate hosts. Thus, the aim of this study was to analyze in vivo development of A. vasorum larval stages in experimentally infected African giant snails (Lissachatina fulica). Adult L. fulica (n = 26) were orally infected with A. vasorum-L1 and thereafter continuously euthanized. Gastropod organs were artificially digested and microscopically analyzed for the presence of A. vasorum larvae. Moreover, paraffin-fixed organs were investigated histologically for snail-borne innate immune response. In the current study, the success of L. fulica oral infection was demonstrated, thereby reaching larval recovery rates of up to 49.7%. During snail infection, an organ tropism of A. vasorum larvae was detected for the lungs and the foot muscular tissue. Overall, A. vasorum-driven gastropod innate immune reactions against larvae varied greatly. In some specimens, larvae were found effectively ensnared by recruited hemocytes, resulting in granuloma formation, whilst in others, hemocyte-mediated reactions were barely observed. Nevertheless, these evidences demand more studies on hemocyte-derived effector mechanisms against A. vasorum.
Keywords: ddc:630